The Effectiveness of Using Pop-Up Books to Enhance Vocabulary Acquisition in Young Learners - Zaenab Faradilla; Yeni Rahmawati* (Riwayat: Educational Journal of History and Humanities, 2024)
This study discusses using pop-up books to enhance vocabulary acquisition in young students. The use of pop-up books is expected to be an effective solution in improving students' learning achievement while providing an interactive and fun learning experience. This study used a quantitative method with a quasi-experimental design. The class selection was randomized using a spin wheel with a population of 61 fifth-grade students of MI At-Taufiq Samarinda East Kalimantan. Students were divided into 2 classes, namely class 5-A as the control group and class 5-B as the experimental group. This study used pre-tests and post-tests to assess students' ability to use pop-up books to improve vocabulary learning. The test was adapted from the Student Worksheet available at school. The post-test results showed the experimental group's mean score was 83.71 with a standard deviation of 13.427, while the control group had a mean score of 57.56 with a standard deviation of 17.328. The normality test using Kolmogorov-Smirnov showed that the control group data followed a normal distribution with a p-value of 0.068. The independent t-test results showed a significance value of 0.000, which means there is a significant effect of using pop-up books on improving vocabulary mastery. Pre-test and post-test were used to measure students' level of understanding before and after the treatment. From the results of the analysis, it can be concluded that pop-up books have a significant effect in improving students' vocabulary mastery.